Effect of environmental tax reform on corporate green technology innovation - Zhang, Chuan; Zou, Cai Feng; Luo, Wenbo; Liao, Lamei (Frontiers in Environmental Science, 2022)
China has recently taken several measures to counter the environmental pollution unleashed by the crude model of past economic development. Among them, taxation has proved especially efficient. We take the Environmental Protection Tax Law, implemented on January 1, 2018, as a quasi-natural experiment, and study the effect of environmental protection tax reform on corporate green technology innovation using the 2013–2020 data on Shanghai and Shenzhen A-share listed companies. We find that raising the tax levy can significantly promote the green innovation of enterprises. The promotion effect is more significant in state-owned enterprises, heavily polluting enterprises, and the eastern region. The findings of the full sample and subsample still hold after replacing the explanatory variables for stability testing. The study confirms that environmental tax reform has a significant promotion effect on green technological innovation among enterprises, although there exists significant heterogeneity in property rights, geography, and level of industry pollution. Nevertheless, environmental tax reform is an effective initiative toward environmental protection, even if the complexity of China’s economic environment reveals some variation in the effects of this policy reform. We make suggestions to address these differences for future studies.